Energy optimization of brushed DC motor in electric power-assisted steering - Danapalasingam, Kumeresan A. (Penerbit UTM, 2014)
Electric power-assisted steering (EPS) is a control system where an electric motor is used to provide assistance in vehicle steering. In this work controllers are designed for a column-type EPS equipped with a brushed DC motor to enable energy optimization. Using a mathematical model of EPS a controller is developed based on nonlinear adaptive regulation method to generate driver torque. PID control is then applied to produce assistance torque in accordance to desired energy saving. Simulation results using Matlab show the trade-off between driver’s comfort and energy consumption. The control paradigm introduced here fits appropriately in electric vehicles (EVs) where electrical energy is scarce.